O desenvolvimento de novos serviços em empresas de manufatura : estudo de casos em produtores de caminhões - Gomide, Eduardo Heber (2017)
Services are not only important for companies in the tertiary sector, but also for manufacturing companies. With the servitization strategy, these companies are offering more services added to their products and developing new service offerings in which the product is no longer the focus on the offer to the customer. The servitization, understood as this process for service-centric business models, requires new postures, processes, capabilities, and resources. Among the processes, manufacturing companies need to start developing not just products, but services as well. With this, the New Service Development (NSD) gains importance for manufacturing companies. In spite of this importance, there is no consensus in the literature about NSD structuring and its integration with the product development process (PDP) in manufacturing companies. Thus, this dissertation sought to focus on the following research questions: How do manufacturing companies organize their New Service Development processes, and how is this process integrated into the New Product Development process? Therefore, the objective is to characterize and analyze the process of New Service Development in the context of manufacturing companies. To achieve this objective, two research strategies were used: Systematic Bibliographic Review and the Multiple Case Study in two manufacturing companies of truck manufacturers. Through semi-structured interviews, the heads of the areas involved with the NSD were interviewed in order to identify information regarding the structuring of the NSD. The results indicate that most of the innovations made by the companies investigated refer to innovations of the ad hoc type and consist in the development of new solutions to the problem of a client. It was also observed that the companies do not have an area dedicated to the NSD, and this responsibility falls on the After Sales area due to the approach with the clients. It is also concluded that the companies do not perform all the steps provided in the traditional models and have low levels of NSD formalization. Finally, on the integration of PDP and NSD processes, there is a positive consensus among companies, but this is understood as the exchange of information. In this way, the results indicate that the processes are performed in a non-integrated way.